Neuroprotective Effects of Alpha-Lipoic Acid in Experimental Spinal Cord Injury in Rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; ERZİK, CAN; AKAKIN, DİLEK; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (TAYLOR & FRANCIS LTD, 2010)
Background: Oxidative stress is a mediator of secondary injury to the spinal cord following trauma. Objective: To investigate the putative neuroprotective effect of a-lipoic acid (LA), a powerful antioxidant, in a rat model of spinal cord injury (SCI). Methods: Wistar albino rats were divided as control, vehicle-treated SCI, and LA-treated SCI groups. To induce SCI, a standard weight-drop method that induced a moderately severe injury (100 g/cm force) at T10 was used. Injured animals were given either 50 mg/kg LA or saline at 30 minutes postinjury by intraperitoneal injection. At 7 days postinjury, neurologic examination was performed, and rats were decapitated. Spinal cord samples were taken for histologic examination or determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity, and DNA fragmentation. Formation of reactive oxygen species in spinal cord tissue samples was monitored by using a chemiluminescence (CL) technique. Results: SCI caused a significant decrease in spinal cord GSH content, which was accompanied with significant increases in luminol CL and MDA levels, MPO activity, and DNA damage. Furthermore, LA treatment reversed all these biochemical parameters as well as SO-induced histopathologic alterations. Conversely, impairment of the neurologic function caused by SCI remained unchanged. Conclusion: The present study suggests that LA reduces SCI-induced oxidative stress and exerts neuroprotection by inhibiting lipid peroxidation, glutathione depletion, and DNA fragmentation.
Keywords: Alpha-lipoic acid; Antioxidants; Spinal cord injuries; Trauma; Neuroprotection; Lipid Peroxidation; Glutathione, Myeloperoxidase; DNA damage; ISCHEMIA-REPERFUSION INJURY; TRAUMATIC BRAIN-INJURY; OXIDATIVE STRESS; DIHYDROLIPOIC ACID; ANTIOXIDANT; METHYLPREDNISOLONE; GLUTATHIONE; PROTECTS